2017
DOI: 10.1074/jbc.m116.759886
|View full text |Cite
|
Sign up to set email alerts
|

Trp-Asp (WD) Repeat Domain 1 Is Essential for Mouse Peri-implantation Development and Regulates Cofilin Phosphorylation

Abstract: Edited by Xiao-Fan WangTrp-Asp (WD) repeat domain 1 (WDR1) is a highly conserved actin-binding protein across all eukaryotes and is involved in numerous actin-based processes by accelerating Cofilin severing actin filament. However, the function and the mechanism of WDR1 in mammalian early development are still largely unclear. We now report that WDR1 is essential for mouse periimplantation development and regulates Cofilin phosphorylation in mouse cells. The disruption of maternal WDR1 does not obviously affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…This overall dephosphorylation of cofilin was also found in Wdr1 knockout mouse cells (Xiao et al, 2017) and in the neutrophils of an LLS patient harboring a D26N mutation in Wdr1 (Kuhns et al, 2016). Xiao et al (2017) were able to explain this effect of Wdr1 deficiency by showing that mouse WDR1 binds to the LIM-kinase (LIMK1) microtubule binding domain, thus preventing its inhibitory localization to microtubules and enhancing its ability to phosphorylate cofilin. Interestingly, even though the two point mutations shown to cause cofilin unphosphorylation, our carmin W540R and the human D26N.…”
Section: Discussionmentioning
confidence: 74%
“…This overall dephosphorylation of cofilin was also found in Wdr1 knockout mouse cells (Xiao et al, 2017) and in the neutrophils of an LLS patient harboring a D26N mutation in Wdr1 (Kuhns et al, 2016). Xiao et al (2017) were able to explain this effect of Wdr1 deficiency by showing that mouse WDR1 binds to the LIM-kinase (LIMK1) microtubule binding domain, thus preventing its inhibitory localization to microtubules and enhancing its ability to phosphorylate cofilin. Interestingly, even though the two point mutations shown to cause cofilin unphosphorylation, our carmin W540R and the human D26N.…”
Section: Discussionmentioning
confidence: 74%
“…We found that phosphorylated Cofilin was distributed at the periphery of the spindle in mouse oocytes, which is consistent with previous studies. 23,50 Previous studies suggested that the interaction of AIP1 with LIMKs PDZ region might regulate Cofilin phosphorylation via LIMKs by inhibiting its binding to the microtubules in mouse embryonic fibroblast cells. 23 They suggest that mouse AIP1 binds to LIMKs and enhances its activity to phosphorylate ADF/Cofilin, which could result in stabilization, rather than disassembly, of actin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, AIP1 is essential for mouse peri-implantation development. 23 AIP1 was identified as a major cofactor that collaborates with ADF/Cofilin-decorated actin filaments and enhances filament disassembly. 6 It binds to the Cofilin-F-actin complex and strongly enhances the severing activity of Cofilin on actin filaments by capping the barbed ends of the severed filaments, resulting in acceleration of actin depolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies show that AIP1 deficiency causes lethality in mice [81,82], insects [17], nematodes [20], and plants [83]. In addition, recessive point mutations in the human WDR1 gene cause severe blood disorders [84,85].…”
Section: Biological Functions Of Aip1mentioning
confidence: 99%
“…Although most of genetic observations are consistent with the function of AIP1 to disassemble ADF/cofilin-bound actin filaments, whether AIP1 has other ADF/cofilin-independent functions remains unknown. A recent study shows that mouse WDR1 binds to LIM-kinase and enhances its activity to phosphorylate ADF/cofilin [82], which could result in stabilization, rather than disassembly, of actin filaments. Therefore, consequences of AIP1/WDR1 up-regulation in cancer and other conditions need to be carefully evaluated in each case.…”
Section: Perspectivesmentioning
confidence: 99%